Whole exome sequencing identified a pathogenic variant c.1620C>G in the FGFR3 gene in a Vietnamese patient - Nguyen, Duc Tien; Nguyen, Thi Thanh Ngan; Nguyen, Ngoc Lan; Tran, Thi Anh Thuong; Can, Thi Bich Ngoc; Vu, Chi Dung; Nguyen, Van Tung; Nguyen, Thi Kim Lien; Nguyen, Thanh Hien; Nguyen, Duc Quan; Tran, Thi Huong Giang; Phan, Ke Long; et al. (Vietnam Journal of Biotechnology, 2025)
Fibroblast growth factor receptor (FGFR3)-related diseases can present a wide spectrum of symptoms, ranging from mild shortening of limbs to lethal skeletal dysplasia. Diagnosing FGFR3-related diseases can be challenging given phenotypic overlap with other skeletal dysplasia. The appropriate diagnosis of FGFR3-related diseases relies on a combination of clinical and radio-imaging data, and molecular analyses. In this report, we present a Vietnamese female with short stature, shortening of long bones, short and broad femoral neck, and squared and shortened ilia. Whole exome sequencing and variant filtering were performed in the proband to identify a disease-causing variant. Sanger sequencing was carried out to confirm the presence of the variant in the proband as well as in her parents. The result showed that a c.1620C>G (p.N540K) in the FGFR3 gene was found in the proband. The parents and sister carried normal alleles. The variant in the proband is de novo. The variant was classified as a pathogenic variant in the ClinVar database. Therefore, the proband was diagnosed with hypochondroplasia. This is the first report of pathogenic variant c.1620C>G (p.N540K) in the FGFR3 gene identified in the Vietnamese patient.